Disseminated histoplasmosis associated with acquired hemophagocytic lymphohistiocytosis. Issue 3 (4th December 2014) - Rajput, Ashish; Bence‐Bruckler, Isabelle; Huebsch, Lothar; Jessamine, Peter; Toye, Baldwin; Padmore, Ruth
Key Clinical Message Hemophagocytic lymphohistiocytosis (HLH) is a potentially life‐threatening clinical syndrome caused by uncontrolled activation of lymphocytes and histiocytes resulting in high levels of cytokines. Acquired HLH occurs in autoimmune, inflammatory, infectious, and immunosuppressive disorders. Prompt identification and treatment of an underlying triggering cause improves clinical outcome.